2017
DOI: 10.1007/s00520-017-3578-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of family members of palliative medicine and hospice patients who experienced music therapy

Abstract: Family members of patients in palliative medicine and hospice settings reported an immediate positive impact of music therapy on the patient and on themselves. More research needs to be conducted to better understand the benefits of music therapy for family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
0
37
0
2
Order By: Relevance
“…The positive effects of music on psychological and physiological outcomes seem to extend to family members of patients as well (e.g. Gallagher et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects of music on psychological and physiological outcomes seem to extend to family members of patients as well (e.g. Gallagher et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…To The Editor, First of all, I would like to congratulate Gallagher and colleagues for their study [1] in which they observed 50 family members to understand family members' perceptions of music therapy experienced by a relative in palliative or hospice care. They concluded that music therapy has a positive impact on the family members of patients and themselves in palliative medicine and hospice settings.…”
mentioning
confidence: 99%
“…Its flexibility and adaptability enable medical workers to work intensively even in a very short period of time to meet the overall needs of patients and their family members. 23 In summary, during hospice care, music therapy has been proven to relieve the physical and emotional suffering of the patients, and it can be used in a variety of environments, is economical, and is environmentally friendly. However, at present, nursing staff in China have limited knowledge and skills in using music as therapy, and lack the resources and ability to implement it.…”
Section: Benefits and Limitations Of Music Therapy In Hospice Carementioning
confidence: 99%